CURRENT IDEAS ABOUT THE POSSIBILITY OF USING TANTALUM AND ITS DERIVATIVES IN MEDICAL PRACTICE (LITERATURE REVIEW) - Кислов, Олександр (SWorldJournal, 2023)
The review of the literature presents modern ideas and achievements regarding the use of tantalum and its derivatives in medical practice. The main physical and chemical properties of tantalum, its biocompatibility and antibacterial properties are highlig